(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Therapeutic Plasma Exchange (TPE) is a very effective modality of treatment for many of the immune-mediated neurological disorders. Objective: The aim of study was to evaluate demographics, indications, adverse reactions and outcome of TPE in patients with neurological disorders. Methodology: This prospective study was conducted in the Department of Transfusion Medicine at National Institute of Neurosciences and Hospital (NINS), Dhaka from January 2023 to December 2023 for a period of one year. All the available data were systematically recorded and these were variables of demographics, clinical indications, numbers of sessions, volume of exchanged plasma, clinical response and complications during or after the procedure. Results: A total number of 110 patients with different neurological disorders had undergone 362 sessions of TPE among which 71 (64.5%) were male. The mean age, number of TPE session and volume of plasma exchange were 33.6±12.3 years (Range 15 to 71), 3.8±1.1 (Range 2 to 7), 2105±320mL (Range 1400 to 3200) respectively. Guillain-Barre Syndrome (GBS) (n=68, 61.8%) was the most common indication of TPE followed by Myasthenia gravis (MG) (n=18, 16.4%). In 362 sessions of TPE, overall incidence of adverse reaction was in 47(12.98%). Allergic reaction (n=15, 4.14%) and hypotension (n=9, 2.48%) were most commonly reported. Reactions were mild and were reversed by bed side managements. Conclusion: A variety of neurological disorders require TPE as a treatment option, with Guillain-Barré Syndrome and Myasthenia gravis being the most common cases in our setting. Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):77-82